New Black Fungus Gnats (Diptera, Sciaridae) of North America. Part III. Genera Camptochaeta Hippa & Vilkamaa, Claustropyga Hippa, Vilkamaa & Mohrig and Dichopygina Vilkamaa, Hippa & Komarova - Mohrig, Werner; Kauschke, Ellen (Zootaxa, 2017)
Seven species of the genus Camptochaeta, two of the genus Claustropyga and one of the genus Dichopygina are newly described from the Nearctic region. These are: Camptochaeta abnormalis sp. n., Cam. camptochaetosa sp. n., Cam. grimaldii sp. n., Cam. multispina sp. n., Cam. praexystica sp. n., Cam. subxystica sp. n., Cam. unispina sp. n., Claustropyga postbrevichaeta sp. n., Cl. subbrevichaeta sp. n. and Dichopygina praeaculeata sp. n. All new species are diagnosed and their distribution data are given. Three species, Camptochaeta duplicata Hippa & Vilkamaa, 1994, Claustropyga abblanda (Freeman, 1983) and Cl. sajanica (Mohrig & Antonova, 1978) are reported for the Nearctic region for the first time. With these new species, Camptochaeta includes 30 species, Claustropyga 15 species and Dichopygina 6 species in the Nearctic region now.